Pengaruh Kemasan Dan Kualitas Produk Terhadap Minat Beli Konsumen Beras Medium (KPSH) di Perum Bulog Kanwil Bali : Studi Pada TPK Merta Jaya Kreneng Denpasar - Rizky Kurniawan Murtiyanto; Maulana Dimas Said (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of packaging and product quality on consumer buying interest in medium rice (KPSH) at Perum Bulog Kanwil Bali. This research is quantitative research. This research uses primary data by distributing questionnaires to 100 respondents who were taken using accidental sampling technique. Respondents were customers of Toko Pangan Kita who had purchased medium rice at Merta Jaya Kreneng Denpasar. This research data analysis uses multiple linear regression analysis. The independent variable consists of packaging and product quality, while the dependent variable is purchase interest. The results of this research show that packaging and product quality have a positive and significant effect on interest in buying medium rice (KPSH) at Perum BULOG Kanwil Bali with the results of the analysis of the coefficient of determination showing a figure of 63.2% and the remaining 36.8% is influenced by other variables not discussed. in this research.